Increasing the Maximum Achievable Strain of a Covalent Polymer Gel Through the Addition of Mechanically Invisible Cross‐Links. (17th July 2014) - Kean, Zachary S.; Hawk, Jennifer L.; Lin, Shaoting; Zhao, Xuanhe; Sijbesma, Rint P.; Craig, Stephen L.
<x xml:space="preserve">Abstract</x> Hydrogels and organogels made from polymer networks are widely used in biomedical applications and soft, active devices for which the ability to sustain large deformations is required. The strain at which polymer networks fracture is typically improved through the addition of elements that dissipate energy, but these materials require extra work to achieve a given, desired level of deformation. Here, the addition of mechanically "invisible" supramolecular crosslinks causes substantial increases in the ultimate gel properties without incurring the added energetic costs of dissipation. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>